2013
DOI: 10.1027/0227-5910/a000182
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Need for Care and Health Care Utilization Among Depressed and Anxious Patients With and Without Suicidal Ideation

Abstract: Abstract.Background: Information is scarce concerning the perceived needs and the amount of health-care utilization of persons with suicidal ideation (SI) compared to those without SI. Aims: To describe the needs and health care use of persons with and without SI and to investigate whether these differences are associated with the severity of the axis-I symptomatology. Method: Data were obtained from 1,699 respondents with a depressive and/or anxiety disorder who participated in the Netherlands Study of Depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Another study found that differences in perceived unmet needs and health care use between persons with a common mental disorder with and without suicidal ideation were largely explained by severity of the symptomatology, as persons with suicidal ideation typically have more severe mental illness. Moreover, even when receiving mental health care, persons with suicidal ideation were more likely to perceive this care as insufficient or inadequate [ 31 ]. In 2019, a total of 46% of suicide attempters in the US reported needing mental health care but did not receive it, and this did not significantly change during the decade [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that differences in perceived unmet needs and health care use between persons with a common mental disorder with and without suicidal ideation were largely explained by severity of the symptomatology, as persons with suicidal ideation typically have more severe mental illness. Moreover, even when receiving mental health care, persons with suicidal ideation were more likely to perceive this care as insufficient or inadequate [ 31 ]. In 2019, a total of 46% of suicide attempters in the US reported needing mental health care but did not receive it, and this did not significantly change during the decade [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Crisis is enormously grateful for the dedication and commitment of Professor Ad Kerkhof, formerly Co-Editor-in-Chief (together with Professors David Clark and John Connolly), who served as an Associate Editor of Crisis until the end of 2012 and has been an active contributor to the journal (see, for example, Kerkhof, 2012; Stringer et al., 2012). For nearly 20 years, Professor Kerkhof has been a driving force behind the journal, and there are no words that could sufficiently acknowledge the work he has done.…”
mentioning
confidence: 99%